Knowledge Management Practices and Employee Performance at DFCU Bank in Uganda - Daphine Asiimwe; Rogers Barigayomwe (East African Nature and Science Organization, 2024)
This study examines the relationship between knowledge management practices and employee performance at DFCU Bank in Uganda. The study is based on the firm's knowledge-based theory, which states that knowledge is a critical resource for organizations and that effective knowledge management can improve organizational performance. A total of 150 employees from DFCU Bank were surveyed to gather data on knowledge management practices and employee performance levels. The results of the study indicate that there is a positive relationship between knowledge management practices and employee performance. Specifically, employees who reported higher levels of knowledge management practices also reported higher levels of employee performance. The study also identified the knowledge management practices that were most effective in improving employee performance at DFCU Bank. These practices include knowledge sharing, training and development, and communication. The findings of this study have important implications for organizations looking to improve employee performance. By implementing effective knowledge management practices, organizations can enhance employee performance, leading to improved organizational performance